2015
DOI: 10.1002/ece3.1519
|View full text |Cite
|
Sign up to set email alerts
|

An approach to consider behavioral plasticity as a source of uncertainty when forecasting species' response to climate change

Abstract: The rapid ecological shifts that are occurring due to climate change present major challenges for managers and policymakers and, therefore, are one of the main concerns for environmental modelers and evolutionary biologists. Species distribution models (SDM) are appropriate tools for assessing the relationship between species distribution and environmental conditions, so being customarily used to forecast the biogeographical response of species to climate change. A serious limitation of species distribution mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…Many species have some degree of behavioral plasticity that allows them to respond to changes in environmental conditions, but modeling these capacities remains challenging (Muñoz et al. ). This behavioral plasticity often leads to behavioral cycles that have important implications for coexistence of competitors (Monterroso et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many species have some degree of behavioral plasticity that allows them to respond to changes in environmental conditions, but modeling these capacities remains challenging (Muñoz et al. ). This behavioral plasticity often leads to behavioral cycles that have important implications for coexistence of competitors (Monterroso et al.…”
Section: Discussionmentioning
confidence: 99%
“…Many species have some degree of behavioral plasticity that allows them to respond to changes in environmental conditions, but modeling these capacities remains challenging (Muñoz et al 2015). This behavioral plasticity often leads to behavioral cycles that have important implications for coexistence of competitors (Monterroso et al 2014), coexistence of predators and prey (Lone et al 2017), and adaptation under climate change (Muñoz et al 2015). For example, Monterroso et al (2014) found that most members of a diverse carnivore community exhibited substantial plasticity in diel activity patterns and that pairwise temporal overlap in species activity declined as the number of predator species present increased.…”
Section: Discussionmentioning
confidence: 99%
“…the date of 50% GWI from the Baltic Sea to the White Sea. This is because of the fact that species can adjust their behavior to climate change through phenotypic plasticity (Muñoz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Around the world, climate change has had significant direct and indirect impacts on terrestrial species, by being a major cause of speciation and species extirpation (Pound & Salzmann, 2017). Many studies have recently focused on the ecological (Etterson & Mazer, 2016;Wikelski & Tertitski, 2016), ethological (Munoz, Marquez, & Real, 2015) and biological changes (Torres-Diaz et al, 2016;Hulme, 2016) in relation to climatic change. For example, various ecosystems are vulnerable to climate change which may induce a broad array of adverse effects such as disturbances of phenological events, food web disruptions, pathogens and disease spread and ultimately, in worst case scenarios, may include extinction risks (Wu, Lu, Zhou, Chen, & Xu, 2016).…”
Section: Introductionmentioning
confidence: 99%